Evaluation of acetaminophen as chemical marker for wastewater contamination / Siti Norbayu Mohd. Subari, Rozita Osman and Norashikin Saim. - Mohd. Subari, Siti Norbayu; Osman, Rozita; Saim, Norashikin (2017)
Acetaminophen, an analgesic drug was evaluated as potential chemical marker for wastewater contamination. Water samples of various sources were analysed using online solid phase extraction liquid chromatography with diode array detector. Acetaminophen was detected in the range of 0.17-1.29 ng/mL in surface water samples contaminated with wastewater. Relatively high concentrations (16.7-74.61 ng/mL) of acetaminophen were observed in water samples from Universiti Teknologi MARA (UiTM) treatment plant monitored from March to August 2014. Positive correlation was obtained between the concentrations of acetaminophen with the students’ population based on UiTM academic calendar.